Tradicar, practical training program in Diabetes for today s cardiologist. (25th November 2020) - Garcia Iglesias, D; Rozado Castano, J; Soroa, M; Barja, N; Junco, A; Adeba, A; Vigil-Escalera, M; Alvarez, R; Capin, E; Rubin Lopez, J.M; Colunga, S; Moris De La Tassa, C; et al.
Abstract: Introduction: Diabetes Mellitus (DM) is an importan Cardiovascular Risk-factor and glucose-lowering drugs have shown to improve cardiovascular prognosis. We believe that specific training programs in DM are necessary, and so we have developed a web platform (Tradicar.es) to guide and provide educational tools. Objectives: To evaluate characteristics of DM patients and the impact on active glycemic control strategies after the continuous training system. Methods: We have created a web platform that allows direct consult with experts in diabetes and cardiology, immediately obtaining a recommendation. In addition, users have to propose a treatment, to evaluate their training progression. Prospectively, all DM patients admitted (Apr/18-Feb/19) were included. Personal history and preadmission, proposed and recommended treatment are recorded. For the comparison between proposed and recommended treatment we used a Cohen kappa, and for the comparison between previous and prescribed treatment, a chi-square test was performed. Results: 117 patients were analyzed, 72 (64.9%) male, with a mean of 70.51 (±16.2) y.o. For other clinical variables see table. An active strategy was taken in 105 patients (89.7%), which resulted in an increased prescription of antidiabetic treatment. Specifically, SGLT2i prescription was significantly increased from 12 (10.9%) to 40 (34.2%) patients, p<0.01. The coincidence index increases from 0.76 (±0.21) in the first 4 months, to 0.9 (±0.2) in the last 4 months, p=0.03. Conclusions: The cardiovascular prognostic impact of new glucose-lowering treatments forces us to to update and expand our DM training. Electronic tools allow immediate contact and are essential to improve the medical care we offer. Funding Acknowledgement: Type of funding source: None